The Urgency of Enacting a Presidential Institution Act as an Instrument for Strengthening Checks and Balances in Indonesia: Urgensi Rancangan Undang-Undang Lembaga Kepresidenan sebagai Instrumen Penguatan Checks and Balances - Ahfi, Zieyad Alfeiyad (Universitas Islam Indonesia, 2025)
This study aims to examine the urgency of resubmitting the Presidential Institution Bill by considering various issues that have arisen in recent years, such as the president's authority in legislation, limitations on presidential involvement in elections, presidential authority during transitional periods, and restrictions on the president in granting amnesty and abolition. The method used is normative legal research with a statutory approach and descriptive qualitative literature study. The research results indicate that due to the absence of a Presidential Institution Law, the president is highly likely to abuse power and the system of checks and balances weakens. First, the president's authority in the field of legislation is still too broad, particularly in issuing Government Regulations in Lieu of Law (Perppu), which could potentially lead to autocratic legalism. Second, there are no regulations regarding limits on the president's political involvement in elections, which could potentially give the president room to favor a particular candidate. Third, there are no restrictions on the president's actions during the transition period (lame duck), which opens the possibility for the president to make legal decisions that could disrupt the country's political stability. Fourth, there are no clear benchmarks for granting amnesty and abolition, which could potentially be used as tools for political transactions.